Cardiac neuropathy development in patients with metabolic syndrome and carbohydrate metabolism disturbances (heart rate variability analysis) - E. V. Minakov; L. A. Kudaeva (Кардиоваскулярная терапия и профилактика, 2010)
Aim. To investigate the early stages of cardiac neuropathy development in patients with metabolic syndrome (MS) and carbohydrate metabolism disturbances, based on the analyses of short segment rhythmogram variation (SSV) and average weighted rhythmogram variation (AWV). Material and methods. In total, 90 patients were divided into three groups: Group I (n=30) included MS patients with impaired glucose tolerance (IGT); Group II (n=30) included MS patients with Type 2 diabetes mellitus (DM-2), with DM-2 duration of 5—10 years; Group III (n=30) included healthy controls. All participants underwent general clinical examination, 24-hour ECG monitoring (Holter-DMS system), with subsequent heart rate variability (HRV) analysis of both traditional (RMSSD, pNN50) and new (SSV, AWV) parameters. Results. Impaired monotonous increase of SSV during HR deceleration was observed in Groups I and II. A substantial AWV reduction was observed in Group II during all monitoring periods. In Group I, circadian AWV values were decreased in the morning and normal in the night. In Group II, RMSSD and pNN50 values were significantly reduced during the 24 hours of the monitoring, while in Group I, these values were normal, with some reduction in the morning. Conclusion. HRV analysis identified early, completely reversible during the night, manifestations of cardiac neuropathy in patients with MS and IGT. A new parameter AWV was more effective than the traditional parameters (RMSSD, pNN50) in diagnosing cardiac neuropathy in MS and IGT patients.